A Study of the Solid-Liquid-Gas Three-Phase Coupling Relationship of Coal, Water and Gas. (15th September 2020) - Yuan, Anying; Huang, Chunhui; Hou, Junling; Zhang, Zhaomin; Pan, Weihui; Duan, Lei; Wu, Quansen
Abstract : At the present time, it is of major significance to study the solid-liquid-gas three-phase coupling relationship of coal, water, and gas in deep-mining stopes in order to prevent and control coal and gas outbursts in high-gas mines. In this study, the influence rules of water on the mechanical characteristics of coal, as well as gas diffusion and migration processes, was examined by combining theoretical analysis and laboratory testing procedures. The results showed that with increases in water content, the mechanical characteristics of coal bodies presented change trends of first increasing and then decreasing. In this study, it was found that the water content levels which corresponded to the maximum shear strength of the coal in the No. 8 coal seam in the study area had ranged between 6.77% and 11.9%, and the water content level corresponding to the extreme point was 8.66%. It was observed that under different water content conditions, the gas desorption speeds of the coal bodies gradually decreased over time. The gas desorption speeds rapidly decreased during the initial desorption stage and then gradually decreased over time. Furthermore, under the different water content conditions, the amount of gas desorption in the coal bodies was observed to gradually increase over time, with the initial desorption amounts displaying rapid increases. Then, with the passage of time, the increase speeds of the gas desorption amount gradually decreased and finally tended to remain at a stable value. It was found that with the increases in water content, the desorption speeds, initial desorption speeds, and desorption amount of gas in the coal bodies continuously decreased. In other words, the water content levels in the coal bodies were negatively correlated with the gas desorption speeds and desorption amounts of the coal bodies. In addition, the gas desorption speeds, initial desorption speeds, and desorption amounts were observed to change more sharply with the increases in water content. The results of this research hold important guiding significance for the improvement of the understanding of the mechanical properties of high-gas coal seams and the implementation of effective gas control measures.